Spatial Inequality and Clustering of Environmental Health Personnel Distribution in East Java: Evidence from Moran's I Spatial Autocorrelation Analysis - Carri Noer Fida Yanik; Wahyu Nur Achmadin; Agung Herdianto (LPPM Politeknik Aceh Selatan, 2026)
The distribution of healthcare workers is a key factor in determining access to and quality of public health services. This study aims to analyze the distribution of healthcare workers in regencies/cities in East Java using a quantitative approach and spatial analysis. Data on healthcare workers (Environmental Health Workers) were obtained from each regency/city and analyzed using descriptive statistics, spatial clustering (High-High, High-Low, Low-High, Low-Low), significance testing, and spatially lagged plots to detect outliers. The results show significant variation among regencies/cities, with the highest concentration in Surabaya City and the lowest in Pasuruan City. Spatial cluster analysis revealed high concentrations in city centers and disparities in remote areas. Statistical significance and spatial outliers strengthen evidence of uneven healthcare worker distribution. These findings provide a scientific basis for planning policies to redistribute healthcare workers, support service equity, and improve service quality across regions. This research emphasizes the importance of data-driven allocation strategies to reduce disparities in healthcare access.